Solar Powered Automatic Waste Management System using LoRaWAN - Ansah, M.R.; Akansake, S.N.; Misbawu, A. (International Conference on Adaptive Science and Technology, 2022)
Solid waste segregation is essential in waste management. This project seeks to present a method of separating four kinds of wastes; metal waste, plastic waste, solid wet waste and paper waste. A short message is sent using LoRaWAN technology to the waste collector alerting him on the status of the waste in the bin. The project has a front ultrasonic sensor which detects the presence of a person 40cm to the bin and then automatically opens the bin for the person to drop the waste. Three sensors made up of inductive and capacitive proximity sensor and a moisture sensor are employed in the dump tray to detect whether the waste is metal, paper or a wet substance and subsequently direct the waste to the appropriate bin. Four other ultrasonic sensors are fitted on top of each of the individual bins to determine the level of the waste in the bins. These four sensors are linked to the front sensor to automatically shut the bin to prevent further addition of waste. A 12volt 60watts solar panel is used to power the system through a lithium rechargeable battery. This project will go a long way to solve the waste challenges wwe have in schools, hotels, hospitals and churches
Research Article
Keywords: Segregator; LoRaWAN; inductive proximity; sensor